Betahistine dihydrochloride quantitative determination in dosage forms by the reaction with sodium 1,2-napthoquinone-4-sulphonate - A.O. Donchenko; S. O. Vasyuk (Zaporožskij Medicinskij Žurnal)
, Objectives. Spectrophotometric method is one of the most convenient methods in pharmaceutical analysis, as it is sensitive, precise and cost effective. Therefore, the aim of the present work was the development of simple and available method for the quantitative determination of betahistine dihydrochloride in dosage forms.